Flood risk zoning using geographical information system case study - Karimi, Parastoo (Acta hydrotechnica, 2022)
Today, there are varieties of methods for determining the risk of flooding in different areas of a catchment. However, the use of GIS-based weighting is receiving increasing attention among researchers. In early 2019, severe and continuous floods occurred in some provinces of Iran. Khorramabad was one of the cities most affected by the floods. Regrettably, during the construction development of Khorramabad city, the minimum distance from roads was violated. In this study, flood risks in the area were zoned using a GIS-weighted overlay algorithm. Flood zoning was done based on various maps indicating factors such as rainfall, distance from the waterway, soil composition, waterway density, slope, soil permeability, land use, and vegetation. The flooding area then was parceled into six categories with return periods of 10, 30, and 50 years. As a result, the city was divided into three critical areas in terms of flood risk. The results indicate that the confluence of the Karganeh and Khorram–Rud rivers lacks sufficient capacity to withstand and repel floods. As a result, the city will suffer severe damage in future floods.
Keywords: določanje poplavnih območij; flood risk zoning; GIS; Khorramabad city; Khorramrud River; mesto Khorramabad; reka Khorramrud; utežno prekrivanje; weighted overlay